Co‐based coordination polymer‐derived carbon nanotubes: Preparation, post‐processing and application in dye adsorption. Issue 9 (12th March 2021) - Lin, Hong‐Yan; Luan, Jian; Lin, Jia‐Feng; Tian, Yuan; Liu, Qian‐Qian
Abstract: Post‐processing methods have been widely reported as an effective method to purify and functionalize the surface of carbon nanotubes (CNTs). We used a new Co‐based coordination polymer (CP) as a catalyst precursor to synthesize multi‐walled CNTs (MWCNTs) by the chemical vapor deposition (CVD) method, and examined the use of acidification, carbonization and functionalization treatments in an attempt to achieve experimental conditions which efficiently functionalize the surface of MWCNTs. Our results indicate that post‐processing methods can efficiently tune the quality and purity of MWCNTs, and these methods play important roles in dye adsorption. Abstract :